Analysis on the role of government internal supervisory apparatus and use of information systems on the achievement of follow-up implementations on audit recommendations by the Audit Board of the Republic of Indonesia on the Government of Manado. - Prasetyawati, Linda Anggraeni; Manossoh, Hendrik; Wokas, Heince R.N. (Yayasan Widyantara Nawasena Raharja, 2024)
The study aims to analyze the role of the Government Internal Supervisory Apparatus as well as the implications of the use of information systems on the achievements of follow-up implementations on audit recommendations by the Audit Board of the Republic of Indonesia on the Government of Manado. The research employs a qualitative method with a case study approach. Data collection is done through in-depth interviews, observations, and documentation studies. The research findings show that the objectives for follow-up monitoring activities have been clearly defined in the Strategic Plan of the Inspectorate of Manado. The Government of Manado is also committed to following up on BPK RI's recommendations. However, there are several obstacles hindering the achievement of the follow-up implementations, including limited human resources and budget constraints at the Inspectorate of Manado, the audited entities lack of understanding of recommendations and requested follow-up documents, and the absence of rewards and punishments for regional entities. The information systems used in the monitoring of follow-up implementations also enhance the effectiveness and efficiency of follow-up monitoring.